Changes in fluid pathways in a calcite vein mesh (Natih Formation, Oman Mountains): insights from stable isotopes. Issue 4 (29th July 2014) - Arndt, M.; Virgo, S.; Cox, S. F.; Urai, J. L.
Abstract: We present a structural, microstructural, and stable isotope study of a calcite vein mesh within the Cretaceous Natih Formation in the Oman Mountains to explore changes in fluid pathways during vein formation. Stage 1 veins form a mesh of steeply dipping crack‐seal extension veins confined to a 3.5‐m‐thick stratigraphic interval. Different strike orientations of Stage 1 veins show mutually crosscutting relationships. Stage 2 veins occur in the dilatant parts of a younger normal fault interpreted to penetrate the stratigraphy below. The δ 18 O composition of the host rock ranges from 21.8‰ to 23.7‰. The δ 13 C composition ranges from 1.5‰ to 2.3‰. This range is consistent with regionally developed diagenetic alteration at top of the Natih Formation. The δ 18 O composition of vein calcite varies from 22.5‰ to 26.2‰, whereas δ 13 C composition ranges from −0.8‰ to 2.1‰. A first trend observed in Stage 1 veins involves a decrease of δ 13 C to compositions nearly 1.3‰ lower than the host rock, whereas δ 18 O remains constant. A second trend observed in Stage 2 calcite has δ 18 O values up to 3.3‰ higher than the host rock, whereas the δ 13 C composition is similar. Stable isotope data and microstructures indicate an episodic flow regime for both stages. During Stage 1, formation of a stratabound vein mesh involved bedding‐parallel flow, under near‐lithostatic fluid pressures. The 18 O fluid composition was host rock‐buffered, whereas 13 C composition was relatively depleted. This may reflect reaction of low 13 C CO2 derived by fluid interaction with organic matter in the limestones. Stage 2 vein formation is associated with fault‐controlled fluid flow accessing fluids in equilibrium with limestones about 50 m beneath. We highlight how evolution of effective stress states and the growth of faults influence the hydraulic connectivity in fracture networks and we demonstrate the value of stable isotopes in tracking changes in fluid pathways. Abstract : Carbon and oxygen stable isotope compositions are a valuable tool to track changes in fluid flow regimes in fracture and vein meshes. During Stage 1, the formation of a strata‐bound crack‐seal vein mesh involved bedding‐parallel flow, under near‐lithostatic fluid pressures. The relative depletion of 13C composition of veins may reflect influx of low 13C CO2 derived from detrital organic matter. Stage 2 fault vein formation is associated with fault‐controlled fluid flow accessing fluids from 50 m beneath the Stage 1 mesh.